Recurrent abdominal pain: when an epileptic seizure should be suspected? - Renata C. Franzon; Camila F. Lopes; Kátia M.R. Schmutzler; Maria Isabel R. Morais; Marilisa M. Guerreiro (Arquivos de Neuro-Psiquiatria)
Recurrent episodes of abdominal pain are common in childhood. Among the diagnostic possibilities are migraine and abdominal epilepsy (AE). AE is an infrequent syndrome with paroxystic episodes of abdominal pain, awareness disturbance, EEG abnormalities and positive results with the introduction of antiepileptic drugs. We present one 6 year-old girl who had short episodes of abdominal pain since the age of 4. The pain was followed by cry, fear and occasionally secondary generalization. MRI showed tumor in the left temporal region. As a differential diagnosis, we report a 10 year-old boy who had long episodes of abdominal pain accompanied by blurring of vision, vertigo, gait ataxia, dysarthria, acroparesthesias and vomiting. He received the diagnosis of basilar migraine. In our opinion, AE is part of a large group (partial epilepsies) and does not require a special classification. Pediatric neurologists must be aware of these two entities that may cause abdominal pain.